2008
DOI: 10.1002/mde.1425
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and the opportunity cost of monopoly

Abstract: Innovation enables monopolists to lower their costs, expand their outputs, and reduce their prices. It is conventional to conclude that social welfare unambiguously increases as a result. Assuming linear demand and marginal cost, this paper shows, however, that innovation raises the opportunity cost of monopoly: as a firm enjoying market power becomes more efficient, greater amounts of surplus are sacrificed by consumers because of the progressive monopolist's failure to produce the new, larger competitive out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In terms of how industry concentration impacts the firm's innovation adoption and implementation, there is no consensus in the literature (Reksulak, Shughart, and Tollison 2008;Teece 1996). Schumpeter (1950) suggests that industry concentration has a positive impact on firms' innovation, as only firms that earn profits in excess of the norm can allocate some of these to innovation.…”
Section: Industry Concentrationmentioning
confidence: 99%
“…In terms of how industry concentration impacts the firm's innovation adoption and implementation, there is no consensus in the literature (Reksulak, Shughart, and Tollison 2008;Teece 1996). Schumpeter (1950) suggests that industry concentration has a positive impact on firms' innovation, as only firms that earn profits in excess of the norm can allocate some of these to innovation.…”
Section: Industry Concentrationmentioning
confidence: 99%
“…Cowan and Vickers found that a monopolist's third-degree price discrimination has ambiguous effects on social welfare. Neumann (1999), Lee (2006), and Reksulak et al (2008) found that welfare loss tends to increase as the monopoly exercises greater power over innovative activities. Kahana and Katz (1990) examined the welfare loss that arises from the rent seeking behavior of a price discriminating monopolist.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study examines the welfare loss generated by monopolies in Fiji and Samoa. Second, this Source: Developed by the authors of this paper by using information from existing literature entry used the Harberger (1954) framework for estimating deadweight loss that was later polarized by Worcester (1973), Jenny andWeber (1983), andReksulak et al (2008). Harberger (1954) framework is one of the most popular and cited studies in the existing literature.…”
Section: Impact Of Government Regulation On Monopoly Behaviormentioning
confidence: 99%
“…Geroski (1990) further listed three reasons to expect a negative direct effect of monopoly on innovation: (1) the absence of active competitive forces, (2) an increase in the number of firms searching for an innovation, and (3) incumbent monopolists enjoying a lower net return from introducing a new innovation (Arrow, 1962;Fellner, 1951;Delbono and Denicolo, 1991). In addition, Reksulak et al (2005) argued that cost-saving innovation raised the opportunity cost of monopoly. As a monopolist with market power became more efficient, greater amounts of surplus were sacrificed by consumers since the former increasingly failed to produce the new and larger competitive output.…”
Section: Literature Reviewmentioning
confidence: 99%